Future power system energy management for zero carbon emissions - You, Zheyu (Nanyang Technological University, 2022)
According to the development trend of the power system, it can be predicted that the wind power, solar energy and some other kinds of renewable power generations will become more popular in the future. Therefore, this dissertation explores the impacts of the addition of renewable power generations on the operation of the power system. At the same time, since carbon neutrality and environmental protection have become a consensus of most countries in the world, the future power system will further move towards the goal of low carbon. So, the factor of carbon emission is also considered in this dissertation.